The Pattern of Hypertension Drug Utilization in Public Health Center in the Medan City - Wahyuni, Sri; K, Khairunnisa; U, Harahap (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Hypertension is a disease thatcan causes death as much as 12.8% worldwide. Hypertension is a silent killer that causes complications in Hypertension patients. Complications can be prevented by using anti-hypertension drugs. The aimed of this study was to describe the pattern of drug utilization in several Public health centers in Medan. Method: This non-experimental study involved 109 hypertension patients using cross-sectional methods. Samples were collected at several health centers in August and September 2020 using convenience sampling techniques. Result: The results showed that the single drug type that was most widely used in this study was the Calcium Channel Blocker (CaCB) group (57.8%). The most widely used combination antihypertension drugs were Calcium Channel Blocker (CaCB) and Angiotensin 2 Recep`tor Blocker (ARB) (15.6%). Conclusion: Based on the study results, it can be concluded that the pharmacologic management of antihypertension uses a single anti-hypertension drug (monotherapy) is more than the use of combination drugs (polytherapy).